2023
DOI: 10.1039/d2qo01406h
|View full text |Cite
|
Sign up to set email alerts
|

Metal-free homo-/cross-anion–cation coupling of cyclic diaryl λ3-bromanes

Abstract: The homo anion-cation of cyclic diaryl λ3-bromanes/diarylbrominiums, which was not reported in previous reports, has been disclosed for the first time. The competitive experiments indicates that the anion-cation coupling is...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…A heterocycle-fused cinnoline, thieno­[2,3- c ]­cinnoline 3q , was also synthesized but in low yield, which was due to the decomposition of iodonium. Except for cyclic iodoniums, rarely reported diaryl λ 3 -bromines also worked well, giving 3r – 3w in 24–78% yields.…”
mentioning
confidence: 95%
“…A heterocycle-fused cinnoline, thieno­[2,3- c ]­cinnoline 3q , was also synthesized but in low yield, which was due to the decomposition of iodonium. Except for cyclic iodoniums, rarely reported diaryl λ 3 -bromines also worked well, giving 3r – 3w in 24–78% yields.…”
mentioning
confidence: 95%
“…14 a We also reported facile access to novel 1,1′-biisoquinolines, which are potential N , N -bidentate ligands. 14 b As part of our ongoing investigations on C–N bond formation and iodoniums, 14 herein, we disclose a hydrazyl–halogen exchange strategy for the formal synthesis of benzo[ c ]cinnolines and azobenzenes from phthalic hydrazide with trivalent cyclic 15 or linear 16 iodine( iii )/bromine( iii ) reagents (Scheme 1E). 3,3′,4,4′-Tetraphenyl-1,1′-biisoquinoline performs as a powerful ligand in tandem C–N coupling for the first time, delivering benzo[ c ]cinnolines with good yields and a broad scope.…”
Section: Introductionmentioning
confidence: 99%
“…In 2021, Wencel-Delord reported the meta -esterification and amination of cyclic diaryl λ 3 -bromanes . During our preparation of this manuscript, Wencel-Delord further reported the meta-O -arylation of phenols involved with cyclic diaryl λ 3 -chloranes, and Li et al also reported a meta -selective cross-anion–cation coupling of cyclic diarylbrominium tosylates with alcohols and phenols . On the basis of our previous research about transition-metal-catalyzed ortho -functionalization of cyclic diaryl iodines, we are interested in further exploring the transition-metal-free meta -functionalization of cyclic diaryl iodines for the construction of 3-phenoxy-1,1′-biphenyl skeletons, which are prevalent in natural products and medicinal chemistry (Scheme c,d) …”
mentioning
confidence: 98%
“…A plausible reaction pathway for this transformation was proposed on the basis of the present results and literature (Scheme ). , Initially, base-mediated deprotonation of 1a and 2a would furnish the phenolate A and benzyne intermediate B under heat, respectively. Next, the O -centered nucleophile would attack the benzyne intermediate B to form a new C–O bond, thereby resulting in the carbanion intermediate C .…”
mentioning
confidence: 99%